Psychometric Properties of Self-Regulated Learning Strategies in Learning English Grammar and English Grammar Self-Efficacy Scales - Truong, Thi Nhu Ngoc (Frontiers in Education, 2022)
The study reports on the psychometric properties of instruments that can measure EFL students’ self-regulated learning strategy use and English grammar self-efficacy and examines the relationship between these two constructs. 350 male and 432 female students, aged between 16 and 17, from two high schools in Vietnam participated in the survey. The participants answered the Questionnaire of Self-Regulated Learning Strategies in Learning English Grammar (QSRLSLEG), and the Questionnaire of English Grammar Self-Efficacy (QEGSE). The disjoint two-stage approach for Partial Least Square-Structural Equation was used to analyze the data. The results showed that the 24-item QSRLSLEG and 8-item QEGSE have face, content, and construct validity and reliability. A moderate relationship between SRL strategies in English grammar learning and English grammar SE was found. Both instruments are reliable and valid assessment tools, providing useful information for researchers and English teachers to investigate important aspects of students’ self-regulation in learning English grammar.